2019
DOI: 10.1166/jnn.2019.16615
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Antibacterial Effects of Silver-Doped TiO2 Prepared by the Peroxo Sol-Gel Method

Abstract: A series of multifunctional silver-doped titanium dioxide (Ag/TiO2) nanocomposites with various silver contents were synthesized by the peroxo sol–gel method using TiCl4 as a precursor and H2O2 as a peptizing agent. The sol was used to coat a glass substrate, thereby forming a thin film. The antiviral and antibacterial activities of the Ag/TiO2 films and their use in the photocatalytic degradation of an aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Figure 2 depicts TEM images of TiO2 and 0.5Cu/TiO2 particles. The morphology of the TiO2 particles prepared via the peroxo sol-gel method is best described as an elliptical shape with particle size of 40-60 nm and 15-30 nm for long and short axes, respectively [3,7,12,[23][24][25]. In Figure 2b, HRTEM image displayed the lattice fringe of TiO2 of 0.327 nm, corresponding to the anatase (101) plane.…”
Section: Characteristic Of Cu-doped Tio2 Particlesmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 2 depicts TEM images of TiO2 and 0.5Cu/TiO2 particles. The morphology of the TiO2 particles prepared via the peroxo sol-gel method is best described as an elliptical shape with particle size of 40-60 nm and 15-30 nm for long and short axes, respectively [3,7,12,[23][24][25]. In Figure 2b, HRTEM image displayed the lattice fringe of TiO2 of 0.327 nm, corresponding to the anatase (101) plane.…”
Section: Characteristic Of Cu-doped Tio2 Particlesmentioning
confidence: 97%
“…For use as antibacterial agents, copper and its compounds achieve antibacterial activity by the accumulation of copper ions within cells, eventually causing degradation of cell membranes [19][20][21]. Using titanium tetrachloride (TiCl4) as a precursor and H2O2 as a peptizing agent, previous studies have proposed a peroxo sol-gel method for the synthesis of neutral TiO2 sol [22][23][24][25]. The advantages of this method include not needing a calcination process to obtain the anatase structure of TiO2, as well as the ability to use H2O2 as an oxidizing agent.…”
Section: Characteristic Of Cu-doped Tio 2 Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the fact that Pt enhances the efficiency of virus adsorption and semiconductor charge separation. Moongraksathum et al ( 2019 ) synthesized silver-deposited titanium dioxide (Ag/TiO 2 ) nanocomposite sol and coated it on a glass substrate to form a thin film. It was found that the sample had almost 100% antiviral effect on H1N1 virus and enterovirus 71 under UVC or visible light irradiation.…”
Section: Metal Oxide-based Nano-photocatalystsmentioning
confidence: 99%
“…[6] [7] [8]. The XPS spectra were collected using Al Kα radiation at a voltage and current of 20 kV and 30 mA, respectively.…”
mentioning
confidence: 99%